2010
DOI: 10.1111/j.1744-6570.2010.01196.x
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Long‐term Firefighter Performance From Cognitive and Physical Ability Measures

Abstract: Firefighters from 1 academy training class were observed for 23 years, beginning with their selection test consisting of a g-saturated written exam (GCA) and firefighting simulations loaded on a strength/endurance (SE) factor. Operational validity coefficients for both GCA and SE were high for training success and remained consistently high for job performance ratings throughout the study. The operational validity for combined GCA and SE predictors was .86 for a composite job rating measure covering 21 years o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 65 publications
(87 reference statements)
2
23
1
Order By: Relevance
“…In the context of public safety occupations, Hunter & Hunter (1984) reported a corrected validity of .42 for general cognitive ability. Subsequent research has reported similar validities for firefighters (Barrett, Polomsky, & McDaniel, 1999;Henderson, 2010) but lower validity for police officers (.27;Aamodt, 2004). Personality traits, in particular conscientiousness, have been found to be…”
Section: Individual Psychological Assessmentmentioning
confidence: 87%
See 1 more Smart Citation
“…In the context of public safety occupations, Hunter & Hunter (1984) reported a corrected validity of .42 for general cognitive ability. Subsequent research has reported similar validities for firefighters (Barrett, Polomsky, & McDaniel, 1999;Henderson, 2010) but lower validity for police officers (.27;Aamodt, 2004). Personality traits, in particular conscientiousness, have been found to be…”
Section: Individual Psychological Assessmentmentioning
confidence: 87%
“…Specifically, the Neuroticism, Agreeableness, and Conscientiousness scales were significant predictors of the first assessment dimension. Assessor judgments were not related to the cognitive ability tests, despite the substantial evidence for the validity of general cognitive ability in public safety (Aamodt, 2004;Barrett et al, 1999;Henderson, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Criterion validity studies have been progressively replaced by content validity studies in firefighter research. This is due to litigation issues, because content validity is easily understandable for judges (Henderson, 2010). Although content validity studies have explanatory power about why a skill is relevant to performing a particular task on a job, they do not provide a quantitative estimation (i.e., statistical evidence), whereas studies of predictive validity do (Schmidt, 2012).…”
Section: Criterion Validity In Firefighter Selection Proceduresmentioning
confidence: 99%
“…Some other interesting efforts can be found in this case from the scientific literature. We refer to the works by Barrett, Polonsky, and McDaniel (1999), Henderson, Berry, and Matic (2007), and Henderson (2010). All this research is focused on the criterion validity of cognitive ability (Barrett et al, 1999;Henderson, 2010) and physical tests (Henderson, 2010;Henderson et al, 2007).…”
Section: Criterion Validity In Firefighter Selection Proceduresmentioning
confidence: 99%
See 1 more Smart Citation